Seen and unseen : what Dorothea Lange, Toyo Miyatake, and Ansel Adams's photographs reveal about the Japanese American incarceration - Partridge, Elizabeth (Chronicle Books, 2022)
Provides a collection of historical images from three photographers documenting what life was like inside the Japanese internment camp of Manzanar during World War II. Dorothea Lange was critical of the internment camp and tried to show the horror of what the people were enduring; Japanese American photographer and camp member Toyo Miyatake smuggled in supplies to build his own camera and documented both difficult and happy events at the camp; and landscape photographer Ansel Adams tried to show the people's resilience and patriotism. Includes historical information accompanying the photos along with a map, resources, and additional information.